When Training is Not Enough: An Appeal to the Work Environment for Transfer of Training in the Bahamian Police Force - Hunter-Johnson, Yvonne O. (International Journal of Bahamian Studies, 2013)
This study focused on law enforcement officers’ perception of factors within a Bahamian law enforcement agency that impede transfer of training. The study design was qualitative. Fifteen participants took part in the study. Data were collected using two focus groups consisting of managers (Sergeants) and subordinates (Corporals and Constables). The analysis used open coding. The overall results of the study revealed that the officers do not perceive the organization as supporting transfer of training. Recommendations were made to promote a supportive work environment. The findings and practical applications are discussed.